Anachronism - Filipovic, Elena; Gregos, Katerina; Argos, Brussel (Brussels : Argos - Centre for Art & Media, 2007)
Belag, Boris ; Bijl, Guillaume ; Buche, Tobias ; Claerbout, David ; ghazi, Babak ; Gmelin, Felix ; Grzeszykowska, Aneta ; von Hausswolff, Carl Michael ; Mahen, Erwan ; Marker, Chris ; et al.
Argos - Centre for Art & Media, Brussels, March 24 to May 26, 2007
kunstcatalogus